Mining Environmental Liability and Its in Situ Treatment with Calcium Oxide for Zinc Removal - Campos Llantoy, Alexander Andre (2023)
Mining environmental liabilities have negative effects on human health, the ecosystem and property. This study was conducted at the Cercapuquio Mining Environmental Liability (MEL) in the district of Chongos Alto. The wastewater analysis was conducted at Universidad Continental and data were obtained on metal content and hydrogen potential. This investigation revealed that the Cercapuquio MEL wastewater had a higher concentration of zinc, 9,916 mg/L, and the pH level was 7.53 (alkaline), which is why this effluent exceeds the maximum permissible limit of the annual average. A neutralizing reagent was also prepared by recycling eggshells, calcined at 1000 °C for 40 min, obtaining quicklime with 61.30% calcium oxide (CaO). For wastewater treatment, the quicklime obtained in neutralizing solution was used, which, when applied to the effluent, had the effect of lowering the zinc concentration from 9.916 mg/L to 0.051 mg/L and the pH from 7.53 to 10.36. The average zinc removal achieved in the effluent is 96%.